Age Related Histological and Histochemical Studies on Cranial Larynx and Associated Glands in Broiler Chicks - Bansal, Shailja (Indian Journal of Veterinary Anatomy, 2019)
A study on histology and histochemistry of the cranial larynx was carried out in 30 broiler chicks of different age groups. The dorsal wall of laryngeal mound and medial wall of laryngeal cleft were lined by stratified squamous non-keratinized epithelium. This epithelium transformed in to respiratory epithelium toward the deeper portion of laryngeal cleft. The thickness of these epithelium increased with advancement of age of broiler chicks. The propria-submucosa was having alveolar type mucous glands which showed a strong positive reaction for acidic  mucopolysaccharides. In each laryngeal mound just below the epithelium, plates of hyalineelastic arytenoid cartilage were found on the dorso-lateral aspect of propria submucosa. Toward the deeper portion of the laryngeal cleft, an hyaline-elastic type cricoid cartilage was found. Below the propria submucosa, striated muscles fibres were also found.